Etnomatematika pada Kegiatan Penanaman Pohon serta Implementasinya dalam Pembelajaran Berbasis Literasi dan Numerasi - Maharani, Israq; Hidayah Putri, Jihan; Adelina Ray, Sukma; Kusyani, Diah (Panrannuangku Jurnal Pengabdian Masyarakat, 2023)
Agriculture is a culture that is very close and attached to Indonesian society. Along with the times, the current cultural situation tends to be unknown to the younger generation. Ethnomathematics exists to bridge between culture and education. This community service aims to describe the ethnomathematical study of tree planting within the scope of reforestation and tree seedlings. This service uses training methods combined with literature studies that use the study of knowledge, ideas and findings contained in the literature so as to provide theoretical and scientific information related to implementation in learning which will later be collaborated with literacy and numeracy-based learning that can make a real contribution to social, economic growth and well-being for individuals and society. By having the skills to be able to apply the understanding of literacy and numeracy in the context of economics, engineering, science, social, and other fields, employment competitiveness and economic welfare will increase.